2009
DOI: 10.1007/s00264-009-0739-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful return to high level sports following early surgical repair of complete tears of the proximal hamstring tendons

Abstract: The purpose of this study was to investigate the outcome of surgical management of acute complete proximal hamstring tendon tears. This was a prospective review of a case series from a tertiary referral centre. Ten patients presenting with complete proximal hamstring tendon tears were confirmed on MRI. All patients underwent surgical exploration and repair of the torn tendons with the aim of returning to normal activities and sports. Isokinetic muscle testing was performed using a dynamometer. The Cybex dynamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
81
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 12 publications
3
81
0
1
Order By: Relevance
“…7,[27][28][29]41 In the present study, 18 (58%) of the patients reported that they had regained preinjury activity level at a mean of 9 months (range, 3-18 months and Cohen et al 13 reported concerns of reinjury as one of the reasons why the patients did not return to all preinjury activities after surgical repair of proximal total hamstring rupture.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…7,[27][28][29]41 In the present study, 18 (58%) of the patients reported that they had regained preinjury activity level at a mean of 9 months (range, 3-18 months and Cohen et al 13 reported concerns of reinjury as one of the reasons why the patients did not return to all preinjury activities after surgical repair of proximal total hamstring rupture.…”
Section: Discussionmentioning
confidence: 84%
“…9,18,27 The mean peak torque of the injured leg for knee flexion was 84% of the uninjured, while the mean total work of the injured leg for knee flexion was 81%. Eighteen (60%) patients had a LSI of < 85% for peak torque hamstring strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tears of the proximal hamstring tendons can be addressed surgically [22]. Surgeons are more likely to recommend repair of proximal hamstring-origin complete avulsions because of the risk for tendon retraction and progressive functional impairment with time [29], whereas the majority of hamstring muscle injuries respond well to nonoperative treatment [5,36].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Occasionally, patients who present with either acute or chronic tears may complain of a pins-andneedles sensation in the sciatic nerve distribution, much like sciatica. 14,15 This may be due to the acute compression of a hematoma in the proximity of the sciatic nerve or chronic scarring and tethering of the tendon to the nerve. Similarly, symptoms of ischial bursitis include buttock pain or hip pain, as well as localized tenderness overlying the ischial tuberosity.…”
mentioning
confidence: 99%